Hubungan Motivasi dan Hasil Belajar Mahasiswa Kedokteran - Rika Lisiswanti; Rossi Sanusi; Titi Savitri Prihatiningsih (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2015)
Background: Motivation is the force that drives a person to do something. Motivation can affect student learning achievement. The purpose of this study was to examine the relationship between motivation and student learning achievement. Method: This research method was a cross sectional survey. The study was conducted at the Medical Faculty of Lampung University. The study population was students that taking Medical Basic Science (MBS) blocks 3. Samples were from all population. The instrument used to assess motivation was Motivated Strategies of Learning Questionnaire (MSLQ). The questionnaire comprises 6 dimensions divided into 31 questions that intrinsic, extrinsic, task value, control of learning beliefs, self-efficacy and anxiety. Learning achievement were measured by the MCQ which. Questionnaire data were taken at the end of the block MBS3, which analyzed using Pearson Product Moment correlation. Results: The correlation between intrinsic motivation and student’s achievement obtained -0.020 with 0.805 significance (p> 0.05). Relationships intrinsic motivation and student’s achievement showed an inverse relationship. Extrinsic motivation and student’s achievement obtained 0.670 with 0.397 significance (P> 0.05). The correlation task value and student’s achievement 0.066 with 0.403 significance (p> 0.05). The correlation control of learning beliefs and student’s achievement of 0.054 with 0.339 significance (p> 0.05). The correlation of self-efficacy and student’s achievement of 0.054 with 0.496 significance (p> 0.05). The correlation test anxiety and student’s achievement -0.060 with 0.447 significance (p> 0.05). The correlation of total score of motivation and student’s achievement 0.034 with 0.670 significance (p> 0.05). All correlation dimension obtained motivation was weak and not significance.Conclusion: The results showed very weak positive correlation between the total score of motivation to learning achievement.